Some New Results for the Sobolev-Type Fractional Order Delay Systems with Noncompact Semigroup. (24th March 2020) - Xiang, Qiaomin; Zhu, Pengxian
Abstract : The topological structure of solution sets for the Sobolev-type fractional order delay systems with noncompact semigroup is studied. Based on a fixed point principle for multivalued maps, the existence result is obtained under certain mild conditions. With the help of multivalued analysis tools, the compactness of the solution set is also obtained. Finally, we apply the obtained abstract results to the partial differential inclusions.